ENGLISH TEACHER TEACHING STRATEGY AT SMAN 1 CIPATAT - Ai Siti Juariyah; Siti Nurulika Gustira; Evie Kareviati (PROJECT (Professional Journal of English Education), 2018)
Teaching strategy can describe effective teachers are always looking for something new to keep their students motivated and engaged. If you’re as a new or experienced teacher, you will feel too much by all of the new educational buzzwords, theories, and new strategies that are out there. Strategy of teaching can be considered as something new that may not be suitable to be applied to your teaching style. In this teaching strategy, an English teacher observed used communicative approach and joyful learning approach. Teaching strategy is the most important to be existed and supported areas of in education field especially in a research. The research reviews concentrates to the whole literature includes research done is not educational settings or focuses on only a partial set of studies that may or may not be valid. There has never become a perfect research review on the achievement of the methods of teaching strategy used at many schools. An extensive search found at the school SMAN 1 Cipatat investigating a teaching method used. At the school, an English teacher observed had taught by communicative approach and joyful learning approach. The result of the teaching strategy used the teacher had a good effect on student achievement. When the effect of teaching strategy used by a teacher with the communicative and joyful learning approach, the strategy promoted the greatest effect namely the class atmosphere was life and interesting. The teacher’s teaching performance was excellent.